Communication Strategy of Jakarta Backpacker Community and Malaysia through Facebook for Tourism Destination Promotion - Arswendi, Riki; Gusfa, Henni; Huey, Nun Shwu; Siang, Tan Gek (Universitas Semarang, 2023)
Introduction: Social media is growing rapidly and is used by individuals, groups and organisations. One of them is Facebook. Facebook is used by individuals, groups, governments, and communities. Including travelling communities such as Jakarta Backpackers and Malaysian Backpacker Buddies who use Facebook as a medium for promoting tourism destinations. Methods: This study is a descriptive qualitative research that approaches the problem by analysing the communication strategy of Backpacker Jakarta and Backpackers Buddies Malaysia through Facebook to promote tourism destinations. The concept of communication strategy is used as a guide in this research. Findings: The communication objectives of the Jakarta Backpacker Community and Malaysian Backpackers Buddies are to provide information and persuade Facebook users both in the Indonesian region and the world community. Facebook was chosen as a medium for sharing information on tourism destinations with consideration of the high number of Facebook users in both Indonesia and Malaysia. Promotion is the main objective of the message on the Jakarta Backpacker and Malaysian Backpackers Buddies Facebook accounts. The inclusion of content reference sources and content sustainability is an effort to create a sense of trust by these two travelling communities. Originality: This research has novelty value because previous research did not focus on the Facebook community strategy in promoting tourism destinations in two countries, namely Malaysia and Indonesia. Whereas previous research focuses on the content used to plan travel. In previous studies, community and member engagement in social media conversations led to positive and negative information about gender-based destinations.